2002
DOI: 10.1016/s1201-9712(02)90163-3
|View full text |Cite
|
Sign up to set email alerts
|

Prospective epidemiologic survey of patients with community-acquired pneumonia requiring hospitalization in Switzerland

Abstract: The microbiological diagnosis in CAP can be established in only about 50% of cases with the combination of several diagnostic tools. Epidemiologic surveys of CAP should be performed on a regular basis, regionally, as a way to improve the management of these infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
3

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 24 publications
2
15
3
Order By: Relevance
“…Table 53–5 8 9 12–14 18 21 22 24 35 37–39 42–44 46 49 50 58 59 61–64 66 67 69–71 73 75 77–87 summarises mortality studies in patients with CAP. Mortality varied from <1% to 48% and was not related to antibiotic resistance.…”
Section: Resultsmentioning
confidence: 99%
“…Table 53–5 8 9 12–14 18 21 22 24 35 37–39 42–44 46 49 50 58 59 61–64 66 67 69–71 73 75 77–87 summarises mortality studies in patients with CAP. Mortality varied from <1% to 48% and was not related to antibiotic resistance.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the studies on the bacterial aetiology for CAP did not specifically address the organisms found in the group of COPD patients. In fact, several studies indicated that COPD was a very common comorbidity in patients with CAP 6,16–18 . It is important to examine the aetiology of concomitant infection as COPD patients with a secondary diagnosis of pneumonia had double the mean hospital LOS compared to those without a secondary diagnosis (14.7 vs. 7.7 days) 19 .…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of lower respiratory tract infections (LRTIs) in adults, which are an important cause of morbidity, remains undetermined in more than 50% of cases (Fine et al, 1999;Garbino et al, 2002;File, 2003), mostly due to limited diagnostic procedures. The prevalence of respiratory viruses in adults is largely unexplored, as most relevant data concern infants and children (Choi et al, 2006;Costa et al, 2006;Kusel et al, 2006;Ma et al, 2006;Ordas et al, 2006;Pierangeli et al, 2007).…”
Section: Introductionmentioning
confidence: 99%